2022
DOI: 10.3389/fonc.2021.777590
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Lobectomy Versus Sublobar Resection for pStage I Geriatric Non-Small Cell Lung Cancer

Abstract: ObjectivesThe choice of resection method for geriatric patients with early-stage non-small cell lung cancer (NSCLC) remains contentious. This study aimed to evaluate survival and perioperative outcomes after thoracoscopic lobectomy resection (LR) or sublobar resection (SR) in patients aged ≥75 years with pathologic stage (pStage) I NSCLC.Materials and MethodsWe retrospectively examined 258 consecutive patients aged ≥75 years with pStage I NSCLC who underwent thoracoscopic tumor resection at our institute from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Low-dose computed tomography (CT) screening has recently increased the detection rate of early-stage lung cancer [1][2][3]. Thoracic surgical resection is the major treatment approach for patients with early-stage lung cancer [4][5][6][7]. Surgical planning may vary from patient to patient owing to different surgical risks across patients.…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose computed tomography (CT) screening has recently increased the detection rate of early-stage lung cancer [1][2][3]. Thoracic surgical resection is the major treatment approach for patients with early-stage lung cancer [4][5][6][7]. Surgical planning may vary from patient to patient owing to different surgical risks across patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a previous study, the type of surgery was not a prognostic factor for either lung cancer-related or non-lung cancer-related OS in geriatric lung cancer patients. 25 However, in a nationwide propensity-matched study, there were significant differences in 1-year or 5-year survival rates among those who underwent different surgical methods for patients with lung cancer. 26 The effect of surgical methods on survival remains controversial.…”
Section: Discussionmentioning
confidence: 97%
“…Studies by Altorki et al, Lin et al also, have shown segmental resection for select early-stage lung cancer patients can provide good outcomes compared to lobectomy [2,3].…”
Section: Introductionmentioning
confidence: 99%